ONLINE AUDIO AND VIDEO MATERIALS FOR TEACHING PROFESSIONALLY ORIENTED LISTENING IN TECHNICAL UNIVERSITIES - О. А. Volkova (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2015)
The article examines the potential of online audio and video materials for teaching professionally oriented listening and formation of students' English communicative competence in technical universities. The introductory part of the article highlights the relatively low profile of listening in ESP and EAP research, and as a consequence, low quality and small quantity of audio and video listening materials used in teaching professionally oriented listening in technical universities. In the main body of the article it is emphasized on the necessity of allocating equal time for the formation and development of all language macro-skills in close integration and on the basis of authentic professionally oriented materials. The role of listening in the development of students' English professionally oriented communicative competence is determined. The potential of authentic audio and video material as a source material for all activities in the process of teaching all language skills is demonstrated. There are also suggested online sources of authentic professionally oriented audio and video materials and key criteria for their selection. In the final part of the article we consider the formation and improvement of English professionally oriented listening competence of students in technical universities through the merging of extensive and intensive listening, and using listening lesson sequences.